Introduction to search engine optimization : a guide for absolute beginners - Kelsey, Todd (Apress, 2017)
Don't be intimidated by all the search engine optimization (SEO) tools out there. You will start out learning about keywords and the importance of quality content and then walk through incremental steps as you try out the tools and master the tips and strategies. If you are completely new to search engine optimization and you want to learn the basics, this guide will introduce you to the content quickly. Introduction to Search Engine Optimization is a detailed guide to the most important tools and skills needed to accurately and effectively utilize search engine optimization. This book covers SEO basics, keyword research, SEO ranking and analytics, Google Analytics, and more. It also includes an overview of how to pursue SEO-related certifications. What You'll Learn: Create a content platform, including blogs and YouTube channels Use keywords to maximize findability and increase search volume Check your SEO rank and other analytics Hunt for duplicate content Set up Google Analytics, including Blogger Utilize Indexing and Webmaster tools/search console.